2014
DOI: 10.4314/bajopas.v6i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of High Risk Human Papillomavirus Infections among Women Attending Gynaecology Clinics in Kano, Northern Nigeria

Abstract: Cervical cancer is the most common female cancer in northern Nigeria, yet the pattern of infection with human papillomavirus, the principal aetiologic agent is unknown. This was a preliminary study conducted in two referral hospitals in order to establish base-line data on the prevalence and risk factors for the infection in Kano state, Nigeria. Fifty (50) randomly selected women aged 18 years and above were recruited from gynaecology clinics in Murtala Muhammad Specialist Hospital and Aminu Kano teaching Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 14 publications
4
26
3
Order By: Relevance
“…This agrees with previous reports of an increased HPV among women who indulge in sexual activity at an early age 25,30,32,41. Acquisition of HPV infection is strongly associated with sexual behavior.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with previous reports of an increased HPV among women who indulge in sexual activity at an early age 25,30,32,41. Acquisition of HPV infection is strongly associated with sexual behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Women with high parity had the least prevalence, as previously reported 39. Low parity was recently reported to be a significant risk factor for acquisition of HPV in northern Nigeria 30. In contrast, Okolo et al,25 in southern Nigeria, observed that the prevalence of HPV increases with increasing parity.…”
Section: Discussionmentioning
confidence: 67%
“…HPV16 and 18 are associated with approximately 71% of all cases of CC, and HPV45 is associated with approximately 6% of additional cases of CC [5]. The prevalence of HPV infection in women varies greatly in the African continent where some of the highest prevalences are found [6]. Both hr-HPV and HIV are sexually transmitted infectious agents, and infection by one of the viruses may accelerate transmission of the other [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In Kenya, over 2000 cervical cancer cases are diagnosed per 100,000 women annually, resulting in an estimated 8,600 deaths in the country each year. [4][5][6][7][8][9][10] Cervical intraepithelial lesions are the precancerous condition of the cervix, which if left untreated, can develop to cervical cancer. These lesions are characterised by abnormal cellular morphology and are detectable by microscopic examination of cervical epithelial cells obtained through Pap smears.…”
Section: Introductionmentioning
confidence: 99%